USP15 targets ALK3/BMPR1A for deubiquitylation to enhance bone morphogenetic protein signalling. Issue 5 (May 2014) - Herhaus, Lina; Al-Salihi, Mazin A.; Dingwell, Kevin S.; Cummins, Timothy D.; Wasmus, Lize; Vogt, Janis; Ewan, Richard; Bruce, David; Macartney, Thomas; Weidlich, Simone; Smith, James C.; Sapkota, Gopal P.
Abstract : Protein kinase ALK3/BMPR1A mediates bone morphogenetic protein (BMP) signalling through phosphorylation and activation of SMADs 1/5/8. SMAD6, a transcriptional target of BMP, negatively regulates the BMP pathway by recruiting E3 ubiquitin ligases and targeting ALK3 for ubiquitin-mediated degradation. Here, we identify a deubiquitylating enzyme USP15 as an interactor of SMAD6 and ALK3. We show that USP15 enhances BMP-induced phosphorylation of SMAD1 by interacting with and deubiquitylating ALK3. RNAi -mediated depletion of USP15 increases ALK3 K48-linked polyubiquitylation, and reduces both BMP-induced SMAD1 phosphorylation and transcription of BMP target genes. We also show that loss of USP15 expression from mouse myoblast cells inhibits BMP-induced osteoblast differentiation. Furthermore, USP15 modulates BMP-induced phosphorylation of SMAD1 and transcription during Xenopus embryogenesis.